Correlation of saliva characteristics and caries in beta-thalassemia major patients - Siti Rusdiana Puspa Dewi; Sherly Septhimoranie; Suryadi Muchzal (Faculty of Dentistry, Universitas Gadjah Mada, 2020)
A patient with beta-thalassemia major is known to have poor oral hygiene and a high risk of caries. Some studies showed that patients with beta-thalassemia have low salivary flow rate and acidic saliva. A reduction in salivary flow rate and pH would increase caries susceptibility. The aim of this study was to determine the correlation between salivary flow rate and pH with DMFT index in patients with beta-thalassemia major. This study was a cross-sectional design. A total of 38 patients with beta-thalassemia major aged more than 12 years old at Dr. Mohammad Hoesin Palembang Hospital were included in this study. Their unstimulated saliva was collected by spitting methods, and the teeth were examined with DMFT Index. The salivary flow rate was expressed as ml/min and the pH was measured using a saliva pH indicator paper. Data were analyzed using Pearson correlation test to determine the correlation between variables. The result showed that the mean age of the patients in this study was 16.6 years old, with a higher number of female patients than males. Patients with beta-thalassemia major had low salivary flow rate (0.72 ml/5 min), acidic saliva (6.34), and high DMFT index (8.34). This correlation was statistically significant (p<0.01). It can be concluded that there is a strong negative relation between DMFT index with salivary flow rate and salivary pH in patients with beta-thalassemia major.